Analysing Opportunities and Challenges in E-Voting using Blockchain: Scalability, Security, and Voter Confidentiality - Shivangi Pandey; Dr Kunal Gupta; M.B. Singh; Kumar Satyam; Deepak Kumar (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
In a free world, Democracy is vital as it empowers citizens of a country to partake in decision-making, ensuring their voices are heard and respected. It fosters fairness, protects human rights, and promotes accountability in governance. Democratic voting is the cornerstone of a free and just society, empowering citizens to have a voice in decision-making. It ensures representation, equality, and accountability, nurturing trust and constancy in governance. The current voting system, existing in most countries relies on ballot papers or electronic voting machines (EVMs). These methods, however, encounter various challenges, such as a lack of transparency and low voter turnout, vote tampering, distrust in the election commission, forgery of voter IDs, delays in result announcements, and significant security concerns.To counter these challenges, countries employed online voting, which gained quite a momentum in the current digital era. Online voting has significant prospective to reduce organizational overheads and boost voter attendance. It removes the necessitate for printing ballot documents or setting up polling stations, enabling voters to cast their ballots from any location with an internet connection. However, in spite of these advantages, online voting systems are handled carefully because of the emergence of new security threats. If even a single vulnerability is discovered, it can result in huge manipulations of vote.E-voting systems must ensure legitimacy, accuracy, security, and ease to be effective for elections. However, their adoption may be hindered by various challenges and potential issues associated with their use.Blockchain technology came into picture and addressed these challenges, providing decentralized nodes for secure electronic voting. It is being used more frequently to develop electronic voting systems because of its benefits in end-to-end verification. This technology serves as an admirable alternative to conventional electronic voting solutions, providing features such as distribution, non-repudiation, and enhanced security.The following paper presents a summary of blockchain-based electronic voting systems. The main goal of this analysis was to evaluate the current landscape of blockchain-based voting research and online voting systems, as well as the challenges linked with them, in order to predict potential future advancements.Our work offers an abstract overview of the proposed blockchain-based e-voting framework and introduces the foundational condtruct and key features of blockchain as they relate to e-voting. As a corollary of this study, it was observed that Blockchain systems have the potential to address certain challenges currently affecting election systems. However, transaction speed and privacy protection remains to be two of the most commonly mentioned concerns in blockchain applications.
Keywords: E-Voting; Blockchain; Security; Privacy; Trust